The Analysis Critical-Thinking Skills of Junior High School Students on Geoscience - Anggraeni Rusmia Putri; Eko Hariyono; Erman (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This research aims to analyze the critical-thinking skill of the junior high school student in Mojokerto. This research describes students geoscience conception by using question instruments related to students' critical-thinking skills. The method that used in this research was pre-experimental design with one-shot case study design and descriptive quantitative approach. The test is done online via google form. The question instrument contains 20 questions related to geoscience concept, disasters, and mitigation materials that have been validated by a validator. This research involved 107 students who were on the 7th grade of junior high school in Mojokerto. The results showed that the analysis related to geoscience knowledge of students got an average of 48.79% which was included as very low category, while the critical-thinking skills got 43% on the interpretation indicator, 52% analysis, 79% evaluation, 40% inferential, explanation. 54%, and self regulation 40% with an average critical-thinking skills of 51% which concluded in the very low category. These critical-thinking skills must be built, especially in geoscience conceptl. The accuracy of the analysis of critical-thinking skills in this research only shows the results in the Mojokerto area.